2012
DOI: 10.4315/0362-028x.jfp-12-012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Individual, Pooled, and Composite Fecal Sampling Methods for Detection of Salmonella on U.S. Dairy Operations

Abstract: The objectives of this study were to estimate the prevalence of Salmonella for individual, pooled, and composite fecal samples and to compare culture results from each sample type for determining herd Salmonella infection status and identifying Salmonella serovar(s). During the U.S. Department of Agriculture National Animal Health Monitoring System Dairy 2007 study, data and samples were collected from dairy operations in 17 major dairy states. As part of the study, composite fecal samples (six per operation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(29 reference statements)
5
12
0
Order By: Relevance
“…A higher prevalence in summer months may be related to heat stress, although such an association may be confounded by cow and management related factors such as increased water/moisture in environment due to feed bunk sprinkler use to mitigate heat stress (Edrington et al, 2009). Nevertheless, the higher prevalence of Salmonella shedding in the summer is in agreement with the previous studies that showed an increased prevalence in the summer months (Wells et al, 2001; Blau et al, 2005; Lombard et al, 2012). However, none of these three studies sampled cows throughout the entire year as was done in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A higher prevalence in summer months may be related to heat stress, although such an association may be confounded by cow and management related factors such as increased water/moisture in environment due to feed bunk sprinkler use to mitigate heat stress (Edrington et al, 2009). Nevertheless, the higher prevalence of Salmonella shedding in the summer is in agreement with the previous studies that showed an increased prevalence in the summer months (Wells et al, 2001; Blau et al, 2005; Lombard et al, 2012). However, none of these three studies sampled cows throughout the entire year as was done in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…The additional sampling of large dairies during the summer months may have biased the results to show a higher prevalence among the larger herds. Using a similar sampling scheme and data from the NAHMS 2007 study conducted between February and August 2007, Lombard et al (2012) reported an overall fecal Salmonella prevalence in individual cows of 14% in dairies across the U.S., with a prevalence of 3.9% in the West region of the U.S. While this prevalence in the West region is similar to that reported in the current study, the lack of random sampling in the Lombard et al (2012) study may have biased their results.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In a study comparing individual, pooled, and composite fecal samples, it was found that composite fecal sampling was more sensitive at the sample level than the other 2 methods, primarily because of the increased number of cattle sampled indirectly through this method. 29 Hence, if one is merely trying to obtain a yes or no answer or identify and track specific serovars, or antimicrobial susceptibility patterns over time, composite fecal samples are typically collected from areas on dairy operations where manure accumulates from a majority of adult animals, such as holding pens, alleyways, and lagoons. 29 Newer techniques for diagnosing Salmonella are based on detection of genetic material from the bacteria, that is, polymerase chain reaction (PCR) techniques.…”
Section: Live Animalmentioning
confidence: 99%
“…The prevalence of Salmonella infections associated with calf diarrhea could reach 18.7-43.5 % and that in calves showing no diarrhea could reach 27.7 % (Moussa et al 2010;Youssef and El-Haig 2012). Salmonella infections in cattle have been reported worldwide (Carrique-Mas et al 2010;Lombard et al 2012;Cho and Yoon 2014). The most frequently isolated serotypes from cattle are Salmonella montevideo, Salmonella typhimurium, Salmonella dublin, Salmonella enteritidis, Salmonella anatum, Salmonella newport, Salmonella cerro, Salmonella kentucky, and Salmonella orion (Alam et al 2009;Brichta-Harhay et al 2011;Strawn et al 2014).…”
Section: Introductionmentioning
confidence: 97%